The notion of focus and its relation to contrast in Catalan Sign Language (LSC) - Navarrete-González, Alexandra (Sensos-e, 2019)
In this paper, we describe the different syntactic and prosodic manual and non-manual markers used in the expression of focus and contrast in LSC. Given that in LSC contrast markers may also be found in topics, we follow Vallduví & Vilkuna (1998) and analyse the notion of contrast as a different dimension, which may also overlap with topics, and we offer an analysis of the expression of contrast in LSC from a unifying semantic-pragmatic perspective. Moreover, following Umbach (2004), we identify three different subtypes of contrast expressed through different combinations of markers. Artigo Completo